New Paradigms of Disability in Social Security Law and Policy in Australia: Implications for Exclusion or Participation - Sarah Parker; Bettina Cass (Disability Studies Quarterly, 2005)
This paper explores transformations in the form, purpose and administration of income support law and policies for people with disabilities in the Australian social security system. It identifies a paradigm change which has reinforced a medicalized model of the concept and measurement of disability within social security law, effectively removing from policy discourse and practice recognition of the social and economic factors that influence the capacity for labor force participation. We examine the ways in which the current welfare reform agenda of the Federal Government has developed a disability discourse which constructs the individual as the 'problem' within the welfare system. Changes to eligibility criteria and assessment procedures for disability income support are increasingly based on conceptions of an impaired body, while, paradoxically, welfare reform is increasingly focused on the necessity to meet 'mutual obligation' through market participation (the key-words of the 'new welfare'). We explore the extent to which these policy transformations in Australia are likely to facilitate or impede market participation for people of working age with a disability. Wherever appropriate, comparisons are made with disability income support and employment programs in the USA.